2012
DOI: 10.1371/journal.pone.0030960
|View full text |Cite
|
Sign up to set email alerts
|

Role of Position 627 of PB2 and the Multibasic Cleavage Site of the Hemagglutinin in the Virulence of H5N1 Avian Influenza Virus in Chickens and Ducks

Abstract: Highly pathogenic H5N1 avian influenza viruses have caused major disease outbreaks in domestic and free-living birds with transmission to humans resulting in 59% mortality amongst 564 cases. The mutation of the amino acid at position 627 of the viral polymerase basic-2 protein (PB2) from glutamic acid (E) in avian isolates to lysine (K) in human isolates is frequently found, but it is not known if this change affects the fitness and pathogenicity of the virus in birds. We show here that horizontal transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 69 publications
1
44
0
Order By: Relevance
“…The finding that this mutation is neutral in ducks may help refine risk assessments, such as those described by Russell et al (2012) (50), and indicates the high probability that this mammalian adaptation motif will be maintained in the avian reservoir. Similarly, Schat et al (2012) (42) concluded that neither disease outcome nor transmission of an HP H5N1 virus in ducks or chickens was altered by PB2 627E or 627K. Their study used a human H5N1 virus isolate of clade 1 (A/Vietnam/1203/2004) which bears 627K.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The finding that this mutation is neutral in ducks may help refine risk assessments, such as those described by Russell et al (2012) (50), and indicates the high probability that this mammalian adaptation motif will be maintained in the avian reservoir. Similarly, Schat et al (2012) (42) concluded that neither disease outcome nor transmission of an HP H5N1 virus in ducks or chickens was altered by PB2 627E or 627K. Their study used a human H5N1 virus isolate of clade 1 (A/Vietnam/1203/2004) which bears 627K.…”
Section: Discussionmentioning
confidence: 99%
“…6) in chicken cells in either genetic backbone. Schat et al (2012) (42) did not investigate transmission of the LP viruses between chickens or ducks, so the biological relevance of the ob- servations in chickens for the maintenance of 627E genotype virus in LP or HP avian influenza viruses in a natural reservoir is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the CS, amino acids in its vicinity, mostly in the HA1 domain, were also important in some H5 viruses (7,8). Moreover, virulence markers that extend beyond the HA exist, mainly in the H5N1 subtype (9)(10)(11). Thus, the virulence of H5 AIV is determined multigenically, requiring an optimal gene constellation for full virulence or host adaptation (12).…”
mentioning
confidence: 99%